1996
DOI: 10.2166/wqrj.1996.048
|View full text |Cite
|
Sign up to set email alerts
|

A Species Tolerance Index for Maximum Water Temperature

Abstract: A weighted species association tolerance index with respect to water temperature (WSATI-WT) is based on the final temperature preferendum (FTP) of each of the fish species present in a locale of a stream ecosystem. The WSATI-WT is a measure of the distributional consequences of “behaviour” or habitat selection of an interactive set of species with respect to temperature and extends the indicator species concept to an entire association of fishes. Several relationships were exploited to estimate the FTP of seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…, 1997; Cox & Rutherford, 2000) to salmonids (Lee & Rinne, 1980). In fact, fishes and other aquatic organisms have specific temperature preferences, which can ultimately determine their distribution within streams (Coutant, 1977; Wichert & Lin, 1996). Water temperature is important for salmonid growth (Edwards, Densem & Russell, 1979; Jensen, 1990; Elliott & Hurley, 1997), for the timing of fish movement (Jensen, Hvidsten & Johnsen, 1998) and emergence (Johnston, 1997; Elliott, Hurley & Maberly, 2000), as well as for the triggering of smolt runs in the spring (Hembre, Arnekleiv & L'Abée‐Lund, 2001).…”
Section: River Water Temperature and Aquatic Habitatsmentioning
confidence: 99%
“…, 1997; Cox & Rutherford, 2000) to salmonids (Lee & Rinne, 1980). In fact, fishes and other aquatic organisms have specific temperature preferences, which can ultimately determine their distribution within streams (Coutant, 1977; Wichert & Lin, 1996). Water temperature is important for salmonid growth (Edwards, Densem & Russell, 1979; Jensen, 1990; Elliott & Hurley, 1997), for the timing of fish movement (Jensen, Hvidsten & Johnsen, 1998) and emergence (Johnston, 1997; Elliott, Hurley & Maberly, 2000), as well as for the triggering of smolt runs in the spring (Hembre, Arnekleiv & L'Abée‐Lund, 2001).…”
Section: River Water Temperature and Aquatic Habitatsmentioning
confidence: 99%
“…If colder refugia (e.g., cold springs or tributaries) were accessible, then coldwater species could probably persist through the warmer-thanaverage summers (e.g., Baird and Krueger 2003), and the fish assemblage would likely reflect the mean conditions. However, if thermal refugia were unavailable, then coldwater fish might disappear and the fish assemblage might more closely reflect the warmerthan-average conditions (e.g., Wichert and Lin 1996). Consequently, the fish assemblage observed during sampling might not match the assemblage predicted from the classification.…”
Section: Estimating the Amount And Distribution Of Thermal Classesmentioning
confidence: 99%
“…Particularly for sites that have maximum water temperatures near a thermal threshold, relatively warm summers may elevate water temperatures and shift the site into a warmer thermal class, whereas relatively cold summers may reduce water temperatures and shift the site into a cooler thermal class. The fish assemblage at the site may vary year to year in response to this temperature variation (Wichert and Lin 1996).…”
Section: Estimating the Amount And Distribution Of Thermal Classesmentioning
confidence: 99%
“…Some studies have mainly focused on the impact of forest harvesting on water temperature while others have focused on fish habitat related issues. For example, studies have found that stream water temperature dynamics can influence many fish habitat conditions including the growth rate of fishes, aquatic invertebrates and others [6] [7]. Stream temperature has also been monitored in order to evaluate the impact of human activities due to urbanization [8], thermal pollution [9], etc.…”
Section: Introductionmentioning
confidence: 99%